Radiographic Imaging to Evaluate Food Passage Rate in Preterm Piglets as a Model for Preterm Infants - Susanne Soendergaard Kappel; Susanne Soendergaard Kappel; Per Torp Sangild; Per Torp Sangild; Per Torp Sangild; Thomas Scheike; Christel Renée Friborg; Magdalena Gormsen; Lise Aunsholt; Lise Aunsholt (Frontiers Media S.A., 2021)
Objectives and study: Gut motility in infants mature with increasing post-menstrual age and is affected by numerous hormonal, immunological and nutritional factors. However, it remains unclear how age and diet influence gut motility and its relation to feeding intolerance and gastric residuals in preterm neonates. Using preterm piglets as a model for infants, we investigated if contrast passage rate, as determined by X-ray contrast imaging, is affected by gestational age at birth, advancing postnatal age and different milk diets.Methods: Contrast passage rate was evaluated using serial abdominal X-ray imaging on postnatal day 4 and 18 in preterm and near-term piglets fed infant formula, colostrum or intact bovine milk, with or without added fortifier (total n = 140).Results: Preterm piglets had a faster small intestinal passage rate of contrast solution at day 4 of life than near-term piglets (SIEmpty, hazard ratio (HR): 0.52, 95%CI [0.15, 0.88], p < 0.01). Formula fed piglets at day 4 had a faster passage rate of contrast to caecum (ToCecum, HR: 0.61, 95%CI [0.25,0.96], p = 0.03), and through the colon region (CaecumToRectum, p < 0.05, day 4) than colostrum fed preterm piglets. The time for contrast to leave the stomach, and passage through the colon in day 4 preterm piglets were slower than in older piglets at day 18 (both, p < 0.05). Adding a nutrient fortifier increased body growth, gastric residuals, intestinal length and weight, but did not affect any of the observed passage rates of the contrast solution.Conclusion: Serial X-ray contrast imaging is a feasible method to assess food passage rate in preterm piglets. Contrast passage rate through different gut segments is affected by gestational age at birth, postnatal age, and milk diet. The preterm piglet could be a good model to investigate clinical and dietary factors that support maturation of gut motility and thereby feeding tolerance and gut health in preterm infants.